Sebuah Perbandingan Perlindungan Hukum Terhadap Korban Tindak Pidana Terorisme di Indonesia dan India - Ramadianto, Anang Riyan (Diktum: Jurnal Ilmu Hukum, 2022)
Terrorism is a crime that is a major threat to the maintenance of every country that poses a danger to security, world peace, and harms the welfare of society. This is inseparable from the suffering of victims of crimes who need legal protection from the state. The purpose of this study is to compare forms of legal protection in the normative and empirical settings given to victims of criminal acts in Indonesia and India. This study uses a qualitative research method with an empirical juridical approach and descriptive analytical research specifications. The research was conducted at the National Counter-Terrorism Agency, Jakarta and the India Center for Victimology and Psychological Studies, New Delhi. The data used include primary data and secondary data. Methods of collecting data through interviews and literature study. The data obtained is processed by data reduction, data display, data categorization. Presentation of data in the form of narrative text descriptions, with qualitative analysis methods. The results of the study indicate that the legal protection of victims of criminal acts in both countries has its advantages and disadvantages, as for legal protection that requires further attention regarding medical assistance, another matter is that the rights of victims of past crimes are limited to 22 June 2021. whereas in India it will not harm the victim. Meanwhile, there are factors that hinder the legal protection of victims of criminal acts in Indonesia and India, seen from (1) the legal substance, namely the Government Regulation of Law no. 5 of 2018 does not yet exist while in India there is no specific regulation regarding psychological and psychosocial rehabilitation, (2) the law is the lack of human resources (HR) in the National Counter-Terrorism Agency (BNPT) while in India there is a shortage of human resources at the National Investigation Agency (NIA) , and (3) legal culture, namely the existence of differences between related differences in India, the lack of legal knowledge of the people regarding their rights. Terrorism is a crime that is a major threat to the maintenance of every country that poses a danger to security, world peace, and harms the welfare of society. This is inseparable from the suffering of victims of crimes who need legal protection from the state. The purpose of this study is to compare forms of legal protection in the normative and empirical settings given to victims of criminal acts in Indonesia and India. This study uses a qualitative research method with an empirical juridical approach and descriptive analytical research specifications. The research was conducted at the National Counter-Terrorism Agency, Jakarta and the India Center for Victimology and Psychological Studies, New Delhi. The data used include primary data and secondary data. Methods of collecting data through interviews and literature study. The data obtained is processed by data reduction, data display, data categorization. Presentation of data in the form of narrative text descriptions, with qualitative analysis methods. The results of the study indicate that the legal protection of victims of criminal acts in both countries has its advantages and disadvantages, as for legal protection that requires further attention regarding medical assistance, another matter is that the rights of victims of past crimes are limited to 22 June 2021. whereas in India it will not harm the victim. Meanwhile, there are factors that hinder the legal protection of victims of criminal acts in Indonesia and India, seen from (1) the legal substance, namely the Government Regulation of Law no. 5 of 2018 does not yet exist while in India there is no specific regulation regarding psychological and psychosocial rehabilitation, (2) the law is the lack of human resources (HR) in the National Counter-Terrorism Agency (BNPT) while in India there is a shortage of human resources at the National Investigation Agency (NIA) , and (3) legal culture, namely the existence of differences between related differences in India, the lack of legal knowledge of the people regarding their rights.